Perbedaan Suhu Tubuh pada BBLR terhadap Lama Durasi Perawatan Metode Kanguru di Ruang Perinatologi Rumah Sakit QIM Batang - Cholifatun; Herry Susanto; Kurnia Wijayant (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Kangaroo mother care is a treatment for low-birth-weight infants that involves direct skin-to-skin contact between the infant and the mother (skin-to-skin contact). This provides health and psychological benefits, particularly in providing warmth to the infant, enhancing maternal bonding, increasing maternal trust and satisfaction, and reducing stress. The difference in body temperature of low-birth-weight infants treated with kangaroo mother care for one hour and three hours. Research Method: The research design used was a quasi-experimental, pre-post test with control group design, which involves administering treatment or intervention to the experimental group and then measuring and analyzing the effects of the treatment. The sample size for this study was 30 people. Bivariate analysis was conducted using the independent t-test and paired t-test. The results showed that the infant's body temperature before the kangaroo mother care intervention was in the below-normal. The infant's body temperature after the intervention was in to normal range. The infant's body temperature after the kangaroo mother care intervention in the one-hour had a p value = 0,000 or <0,05). The infant's body temperature after the intervention was in to normal range. The infant's body temperature after the kangaroo mother care intervention in the three-hour had a p value = 0,000 or <0,05). The infant's body temperature after the kangaroo mother care intervention in the one-hour had a p value = 0,000 or <0,05). The infant's body temperature after the kangaroo mother care intervention in the three-hour had a p value = 0,000 or <0,05).